2022
DOI: 10.21203/rs.3.rs-565609/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence and determinants of anemia among pregnant women receiving antenatal care at District Hospital in Qarbagh District, Ghazani Province, Afghanistan

Abstract: Background: The burden of anemia among pregnant women is high in developing countries, with an increased risk of maternal mortality and morbidity in these settings.Objectives: The study aimed to assess the prevalence and determinants of anemia among pregnant women receiving antenatal care at District Hospital in Qarabagh District, Ghazani province, Afghanistan.Methods: Pregnant women receiving antenatal care in this cross-sectional study completed a structured questionnaire and Hemoglobin (Hb) measurement from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…in 2022 at Qarabagh District, Ghazani province, Afghanistan was conducted to evaluate the prevalence of anemia among 625 pregnant women receiving antenatal care. This study reported that factors such as household income, husband’s employment status, menstruation cycle, previous pregnancy complications and education impacted prevalence on anemia in Afghanistan 41 . Compared to Pakistan, the same factors do apply, which affect the incidence of anemia among pregnant women.…”
Section: Comparing Pakistan With Other South Asian Countriesmentioning
confidence: 91%
“…in 2022 at Qarabagh District, Ghazani province, Afghanistan was conducted to evaluate the prevalence of anemia among 625 pregnant women receiving antenatal care. This study reported that factors such as household income, husband’s employment status, menstruation cycle, previous pregnancy complications and education impacted prevalence on anemia in Afghanistan 41 . Compared to Pakistan, the same factors do apply, which affect the incidence of anemia among pregnant women.…”
Section: Comparing Pakistan With Other South Asian Countriesmentioning
confidence: 91%